Production and Perception of German Word Stress by Indonesian Learners of German: A Suprasegmental Study - Robbyanti, Rafika; Lethulur, Budi Aris; Akihary, Wilma (Nexus Publishing NXP, 2025)
In foreign language learning, understanding is not limited to basic sounds such as vowels and consonants, but also includes suprasegmental features that influence meaning and clarity in communication. One important suprasegmental feature is word stress. For Indonesian learners of German, applying correct word stress often presents a particular challenge. This study aims to examine how learners perceive and produce word stress in the German language. A descriptive qualitative methode with an auditive phonetic approach was employed to investigate the perception and production of word stress as a suprasegmental element in German. Data were collected in two stages: (1) a production task involving the oral reading of words and pseudowords, which were analyzed auditorily, and (2) a perception task in which participants listened to recorded words and identified the position of stress. The analysis compared the accuracy of participants’ production and perception and identified common patterns of error. The findings are expected to serve as a basis for developing more contextual and learner-oriented suprasegmental phonetics teaching materials for Indonesian learners of German.